Networks as a social communication space for virtual education in students with disabilities in Costa Rica in pandemic times - Deliyore Vega, María del Rocío (Historia y Comunicación Social, 2021)
This article presents a qualitative, phenomenological type research involving five professionals, four special education teachers and an occupational therapist, who were in charge of students with cognitive disabilities in the period of the COVID 19 pandemic in the year 2020. The objective of the study was to recognize the experience of teachers about the use of social communication networks for educational purposes, with their students with intellectual disabilities. For this, in-depth interviews were conducted that inquired about the organization of services, the barriers that people with disabilities faced to communicate through social networks for virtual education, the successful mediation strategies that they developed to solve these barriers, and the most profitable platforms for the student body. As a result of the research, the participating teachers describe their experience in the use of social communication networks for educational purposes in times of pandemic, with their students with disabilities, as a complex and constantly changing experience, which was subjected to a series of circumstances such as the dominance of people with disabilities in the use of the networks, the support they received from their families; who in turn had different levels of knowledge about the platforms, the conditions of confinement and poverty, the surcharge of functions of women mothers and caregivers to be able to attend virtual education at home and offer access to social communication networks their sons and daughters, among others. On the other hand, it is found that some conditions that the participants live may threaten an increase in the inequality gap, among these, it is found that the time they can dedicate to synchronous care and communication with networks for the education of people with disabilities is significantly lower than that of other student groups without disabilities and with less vulnerability indexes. Despite all this, it is concluded that the global situation in the face of the pandemic encourages innovation and teaching creativity, which makes the student body, even in small proportions; Get familiar with and get used to the use of social communication networks, which facilitates both your learning and opportunities for social inclusion.